The impact of perception regarding therapeutic exercises and dietary changing adherence of subjects known with low back pain (Balneo and PRM Research Journal, 2022)
Debates regarding the role of therapeutic exercises and diet as modulators of an anti-inflammatory state occurred in the last years in the medical environment. The synergy between moderate-intensity exercise and a proper diet targeting decreasing IL-1 inhibits the production of the pro-inflammatory cytokine TNF-α,  the key regulator of local and systemic inflammation. One of the most important causes of short and long-term disability in all occupational groups is back pain, impacting the quality of life. Degeneration of the intervertebral disc (IVD) causes low back pain that intensifies with age. Assessment of the Oswestry Disability Index was applied on 23 subjects with low back pain to investigate the degree of disability. Nutrition of  IVD,  implying therapeutic exercises, and a customized diet may be crucial adjuvants for the rehabilitation process. The appropriate diet and therapeutic exercise approach are meant to evaluate the impact of awareness regarding the possibility of improving health outcomes. In this present study, women have a strong positive Pearson correlation (p